Islamic Religious Education Literacy and Numeration In the Perspective of the Al-Quran and Hadith - Ainur Rofiq Sofa; Mukni’ah; Mashudi (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2022)
The word Iqra 'is usually translated as